Patient profile and quality of services at the accident and emergency unit of the Teaching Hospital Kurunegala - Ranaweera, S.P.A.L (My University, 2007)
The morbidity and mortality trends are changing and demands new service delivery priorities_ Up to late 1980's patients were directly admitted from out patient department to the respective wards. Since then separate accident and emergency service units with direct admissions has been established in some state hospitals. However there was no type plan or recommended minimum resources for these emergency units. Treatment protocols and standard operation procedures used varied from hospital to hospital. Ministry of Health has recently identified improvement of accident and emergency services as one of the top priorities. In 2002 Ministry of Health established a separate Accident and Emergency unit at Teaching Hospital Kurunegala in order to provide good quality emergency services to the patients was selected for this study. Data on selected sociodemographic characteristics and morbidity pattern, timeliness of service and patient's level of satisfaction were collected from patients using interviewer administered questioners. Another sample of fifty (50) members were selected from Accident and Emergency unit staff by using stratified random sampling technique in order to collect data for making recommendations of future improvements to Accident and Emergency unit Teaching Hospital Kurunegala. For continuous variables, mean, mode, median and standard deviations were computed. For categorical variables frequencies and 95 percent confidence interval were calculated. To determine the patient's level of satisfaction five point Lickert Scale that ranged from - 2 to +2 was used. Results of this study showed that the age of patients admitted ranged from neonates to 90 years with mean age of 38.57 ± 22.06SD.